Anthropology as an Educational Practice and Its Current Challenges - Kadir, Hatib Abdul; Pamungkas, Alim Harun (Universitas Negeri Padang, 2020)
This research argues philosophically that anthropology is education itself. Anthropology is the study of other people. The method of producing knowledge is done by the participatory observation method, which is paying attention to other people’s culture and their world. Educations as teaching to know other people and their feelings, or Ingold called as “hapticality”, which is the articulation of knowledge that can be shed through symbols, words, speech, poetry, graphics, charts, to mathematical formulations. Whereas in anthropology, what is done in hapticality is paying attention to the activities and what informants say and what they respond to. Furthermore, see how humans have conversations with life itself.